A rare case of congenital fibrosis of extraocular muscle type 1A due to KIF21A mutation with Marcus Gunn jaw-winking phenomenon. (November 2015) - Kaçar Bayram, Ayşe; Per, Hüseyin; Quon, Jennifer; Canpolat, Mehmet; Ülgen, Ege; Doğan, Hakkı; Gumus, Hakan; Kumandas, Sefer; Bayram, Nurettin; Bilguvar, Kaya; Çağlayan, Ahmet Okay
Abstract Background Congenital fibrosis of the extraocular muscles (CFEOM1) is classically a congenital, non-progressive, restrictive strabismus syndrome characterized by bilateral ptosis and ophthalmoplegia with an infraducted position of the globes. This autosomal dominant syndrome is caused by mutations in the KIF21A gene. Methods and results In this report we describe a 5-year-old boy, and his mother, both of whom have a mutation in the KIF21A gene, who possesses typical features of CFEOM1 syndrome. Besides displaying typical features of CFEOM1, he demonstrated Marcus Gunn jaw-winking phenomenon. The patient additionally had a positive family history of such features. Conclusion This is first report of the coexistence of CFEOM and Marcus Gunn jaw-winking phenomenon in a patient with a KIF21A mutation from Turkey. We explain the phenotypic findings associated with mutations in KIF21A including CFEOM1A and Marcus Gunn jaw-winking phenomenon.